Image quality improvement for digital still cameras : demosaicking and de- ringing - Wang, Xiaomeng (2008)
The digital still color camera has become a popular consumer product for capturing natural images. In a typical digital camera, the image is captured, processed, and then stored on the camera. To achieve cost reduction and compact design, digital still color cameras capture the visible spectrum by using a color filter array (CFA) overlaid on a single-sensor such that each pixel samples only one color channel (red, green or blue). The values of the other color channels must be interpolated using neighboring samples. This color plane interpolation is known as demosaicking. In order to maximize the efficiency of storage in a digital camera, images are usually compressed using a standard image compression algorithm, such as JPEG (Joint Photographic Experts Group).